Conceptualizing Resilience - Birkland, Thomas A. (2016)
This commentary provides an overview of the idea of resilience, and acknowledges the challenges of defining and applying the idea in practice. The article summarizes a way of looking at resilience called a “resilience delta”, that takes into account both the shock done to a community by a disaster and the capacity of that community to rebound from that shock to return to its prior functionality. I show how different features of the community can create resilience, and consider how the developed and developing world addresses resilience. I also consider the role of focusing events in gaining attention to events and promoting change. I note that, while focusing events are considered by many in the disaster studies field to be major drivers of policy change in the United States disaster policy, most disasters have little effect on the overall doctrine of shared responsibilities between the national and subnational governments.